Hard carbon negative electrode material of fast-charging sodium-ion battery and preparation method of hard carbon negative electrode material

By doping nickel-cobalt metal oxides into the hard carbon anode material of sodium-ion batteries and forming a cross-linked polyaniline composite gel structure, the problems of low capacity and poor cycle performance of hard carbon anode materials are solved, and the performance of fast-charging sodium-ion batteries with high capacity and stable cycle is achieved.

CN119263257AActive Publication Date: 2025-01-07JIANGSU CHUANYI NA ION BATTERY RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411388609.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Existing hard carbon anode materials for fast-charging sodium-ion batteries suffer from low capacity and poor cycle performance, which limits their widespread application in practical applications.

Method used

The melamine-formaldehyde resin was prepared by reacting melamine and formaldehyde, and then mixed with urea and calcined to form high-nitrogen hard carbon microspheres. The microspheres were then subjected to pore-expansion treatment with hydrochloric acid solution, followed by loading with nickel-cobalt metal oxides. Finally, the hard carbon microspheres were coated with a cross-linked polyaniline composite gel structure formed by sodium alginate and aniline, which improved the conductivity and structural stability of the material.

Benefits of technology

It significantly improves the charge/discharge rate and cycle stability of sodium-ion batteries, extends battery life, and meets the requirements for fast charging and high energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005071755490000151
    Figure BDA0005071755490000151
Patent Text Reader

Abstract

The invention relates to the field of sodium ion batteries, in particular to a hard carbon negative electrode material of a fast-charging sodium ion battery and a preparation method of the hard carbon negative electrode material, which are used for solving the problem that the popularization of the sodium ion battery in practical application is limited due to the defects of low capacity and poor cycle performance of the existing hard carbon negative electrode material of the fast-charging sodium ion battery. The nickel-cobalt metal oxide is doped into the nitrogen-containing hard carbon microspheres, so that the conductivity and reaction kinetics of the material can be improved, the theoretical capacity of the material is further improved, the charge-discharge rate of the sodium-ion battery can be remarkably improved, and the electrochemical performance of the battery is enhanced; and after being coated by the composite gel structure, the composite gel structure can effectively improve the structural stability of the material, reduce the volume change of the material in the cycle process, remarkably improve the cycle stability of the sodium-ion battery, and maintain longer cycle life and higher capacity retention rate while realizing quick charging. The service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium ion batteries, and in particular to a hard carbon negative electrode material for a fast-charging sodium ion battery and a preparation method thereof. Background Art

[0002] With the rapid development of new energy industries such as electric vehicles and energy storage power stations, the demand for high-performance, low-cost and long-life energy storage devices is increasing. Sodium-ion batteries have become an important supplement to lithium-ion batteries due to their abundant resources and low cost, and play an increasingly important role in promoting energy transformation. As a key component of the battery, the performance of the negative electrode material directly affects the battery's charging and discharging efficiency, capacity and cycle life. As a potential negative electrode material for sodium-ion batteries, hard carbon has good safety and low cost advantages, but its electrochemical performance is not ideal, resulting in limited capacity and rate performance, and it is difficult to meet the needs of fast charging. After research, other metal oxides are loaded into the hard carbon structure, which can regulate its electrochemical properties and improve its conductivity and capacitance. However, during the cycle of loaded metal oxides, the material shows obvious volume expansion / contraction, resulting in the pulverization of the electrode material structure, and then the battery specific capacity also drops rapidly, resulting in poor cycle performance.

[0003] Therefore, it is of great significance to develop a hard carbon negative electrode material for fast-charging sodium-ion batteries with both high capacity and excellent cycle stability and a preparation method thereof. Summary of the invention

[0004] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a hard carbon negative electrode material for a fast-charging sodium ion battery and a preparation method thereof, which solves the shortcomings of the existing hard carbon negative electrode materials for fast-charging sodium ion batteries, such as low capacity and poor cycle performance, which limits the promotion of sodium ion batteries in practical applications.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery comprises the following steps:

[0007] Step 1: adding melamine and formaldehyde solution to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introducing nitrogen protection, stirring and reacting for 20-25 minutes at a temperature of 20-25° C. and a stirring rate of 300-400 r / min, then heating to 60-65° C. and continuing to stir and react for 2-3 hours, then adding polyvinyl alcohol, deionized water and anhydrous acetic acid and continuing to stir and react for 1-1.5 hours, cooling the reaction product to room temperature after the reaction is completed, then centrifuging, washing the precipitate with distilled water and anhydrous ethanol for 2-3 times in sequence, then placing it in a vacuum drying oven, and drying it at a temperature of 50-55° C. for 2-3 hours to obtain melamine formaldehyde resin;

[0008] Step 2: After melamine formaldehyde resin and urea are mixed evenly, they are placed in a tubular furnace, nitrogen is introduced for protection, and the temperature is raised to 700-800°C at a heating rate of 1-2°C / min and calcined for 5-6 hours, and then cooled in the furnace to obtain high nitrogen hard carbon microspheres;

[0009] Step 3: Add high nitrogen hard carbon microspheres and hydrochloric acid solution to a three-necked flask equipped with a stirrer and a thermometer, and perform ultrasonic treatment for 30-40 minutes at an ultrasonic power of 200-250W, and then stir the reaction at a temperature of 40-45°C and a stirring rate of 300-400r / min for 2-3 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then allowed to stand for 2-3 hours, and then centrifuged. The precipitate is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 70-75°C for 4-5 hours to obtain expanded pore hard carbon microspheres;

[0010] Step 4: Add nickel nitrate hexahydrate, cobalt acetate tetrahydrate and deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 25-30 minutes at a temperature of 20-25°C and a stirring rate of 300-400r / min, then add pore-expanded hard carbon microspheres, polyvinyl pyrrolidone and ethylenediamine and continue to stir and react for 5-10 minutes, then heat to 150-160°C and continue to stir and react for 5-6 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 2-3 times, then place it in a vacuum drying oven, dry it at a temperature of 80-85°C for 6-8 hours, then place it in a tubular furnace, heat it to 450-550°C at a heating rate of 1-2°C / min and calcine it for 3-4 hours, then cool it with the furnace to obtain loaded hard carbon microspheres;

[0011] Step 5: Add sodium alginate and deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 1-2 hours at a temperature of -5-0°C and a stirring rate of 300-400r / min, then add calcium chloride solution and continue stirring and reacting for 20-30 minutes, then add loaded hard carbon microspheres, aniline and sodium dodecyl sulfate and continue stirring and reacting for 40-50 minutes, then add ammonium persulfate solution dropwise while stirring, control the dropping rate to 1-2 drops / s, continue stirring and reacting for 6-8 hours after the addition is completed, and then freeze-dry to obtain a hard carbon negative electrode material for a fast-charging sodium ion battery.

[0012] As a further solution of the present invention: the usage ratio of the melamine, formaldehyde solution, polyvinyl alcohol, deionized water and anhydrous acetic acid in step 1 is 10-12 g: 50-55 mL: 2-5 g: 100-120 mL: 6-8 mL.

[0013] As a further solution of the present invention: the mass fraction of the formaldehyde solution in step 1 is 37-40%.

[0014] As a further solution of the present invention: the usage ratio of the melamine formaldehyde resin and urea in step 2 is 10g:0.3-1.9g.

[0015] As a further solution of the present invention: the usage ratio of the high nitrogen hard carbon microspheres and the hydrochloric acid solution in step three is 5g:80-100mL.

[0016] As a further solution of the present invention: the mass fraction of the hydrochloric acid solution in step 3 is 5-15%.

[0017] As a further solution of the present invention: the usage ratio of the nickel nitrate hexahydrate, cobalt acetate tetrahydrate, deionized water, expanded pore hard carbon microspheres, polyvinyl pyrrolidone and ethylenediamine in step four is 10mmo l:10mmo l:150-180mL:8-10g:0.1-0.15g:0.2-0.6mL.

[0018] As a further scheme of the present invention: the dosage ratio of the sodium alginate, deionized water, calcium chloride solution, supported hard carbon microspheres, aniline, sodium dodecyl sulfate and ammonium persulfate solution in step five is 0.25-0.75g:45-50mL:20-30mL:10g:0.42-0.88g:0.02-0.04g:10-15mL.

[0019] As a further solution of the present invention: the molar concentration of the calcium chloride solution in step five is 0.2-0.6 mol / L.

[0020] As a further solution of the present invention: the mass fraction of the ammonium persulfate solution is 1.5-2.5%.

[0021] As a further solution of the present invention: the hard carbon negative electrode material for fast-charging sodium-ion battery is prepared according to the preparation method of the hard carbon negative electrode material for fast-charging sodium-ion battery.

[0022] Beneficial effects of the present invention:

[0023] The present invention discloses a fast-charging sodium-ion battery hard carbon negative electrode material and a preparation method thereof. A nucleophilic addition reaction occurs between melamine and formaldehyde to produce hydroxymethylated melamine, which is then subjected to a polycondensation reaction to form a polymer to obtain a melamine formaldehyde resin. The melamine formaldehyde resin and urea are then mixed and calcined. The melamine formaldehyde resin has a high nitrogen content, and the hard carbon after calcination has a high nitrogen content. After calcination with urea, nitrogen is further doped therein to increase active sites, thereby improving the conductive performance to obtain high-nitrogen hard carbon microspheres. The high-nitrogen hard carbon microspheres are then treated with a hydrochloric acid solution to remove impurities in the high-nitrogen hard carbon microspheres, thereby achieving pore expansion and pore increasing effects to obtain pore-expanding hard carbon microspheres. Nickel nitrate hexahydrate and cobalt acetate tetrahydrate are then used as metal ions, which can be doped into the pore-expanding hard carbon microspheres after calcination. The micropores and the surface loading of nickel and cobalt bimetallic oxides are formed to obtain loaded hard carbon microspheres. Finally, the loaded hard carbon microspheres are treated with sodium alginate and aniline. Sodium alginate can undergo a complexation reaction under the action of calcium chloride to improve the degree of crosslinking. At the same time, a large amount of calcium ions are introduced. After the calcium ions are dissociated, their conductivity can be effectively improved. Then, the amino groups in aniline and the hydroxyl and carboxyl groups of sodium alginate interact with each other through hydrogen bonds, causing aniline to be adsorbed on the surface of sodium alginate. Then, under the action of ammonium persulfate initiator, aniline is directly polymerized on the surface of sodium alginate to generate polyaniline, so that polyaniline and cross-linked sodium alginate can be entangled with each other to form a three-dimensional network composite gel structure with high mechanical strength, which is coated on the surface of the loaded hard carbon microspheres to obtain a hard carbon negative electrode material for a fast-charging sodium ion battery.

[0024] The fast-charged sodium-ion battery hard carbon negative electrode material of the present invention can improve the conductivity and reaction kinetics of the material by doping nickel-cobalt metal oxides into nitrogen-containing hard carbon microspheres, thereby improving the theoretical capacity of the material, significantly improving the charge and discharge rate of the sodium-ion battery, and enhancing the electrochemical performance of the battery. Moreover, after being coated with a composite gel structure, the structural stability of the material can be effectively improved, and the volume change of the material during the cycle process can be reduced, thereby improving the cycle stability of the material and reducing the heat accumulation of the sodium-ion battery during the fast-charge process. It can significantly improve the cycle stability of the sodium-ion battery, and can achieve fast charging while maintaining a long cycle life and a high capacity retention rate, thereby extending the service life of the battery;

[0025] In summary, after the use of this fast-charging sodium-ion battery hard carbon negative electrode material in sodium-ion batteries, it can greatly improve the comprehensive performance of sodium-ion batteries, thereby providing key material support for high-efficiency and faster-charging sodium-ion batteries, and meeting the urgent needs of modern portable electronic devices and electric vehicles for fast charging and high-energy density batteries. Moreover, the preparation method is simple and easy, with low cost, and is suitable for large-scale production. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1:

[0028] This embodiment is a method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery, comprising the following steps:

[0029] Step 1: add 10g of melamine and 50mL of a 37% formaldehyde solution into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir and react for 20min at a temperature of 20°C and a stirring rate of 300r / min, then heat to 60°C and continue stirring and reacting for 2h, then add 2g of polyvinyl alcohol, 100mL of deionized water and 6mL of anhydrous acetic acid and continue stirring and reacting for 1h, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water and anhydrous ethanol twice in sequence, then place it in a vacuum drying oven, and dry it at a temperature of 50°C for 2h to obtain melamine formaldehyde resin;

[0030] Step 2: 10 g of melamine formaldehyde resin and 0.3 g of urea were mixed evenly and placed in a tubular furnace, nitrogen was introduced for protection, and the temperature was raised to 700 ° C at a heating rate of 1 ° C / min and calcined for 5 hours, and then cooled with the furnace to obtain high nitrogen hard carbon microspheres;

[0031] Step 3: Add 5 g of high nitrogen hard carbon microspheres and 80 mL of 5% hydrochloric acid solution into a three-necked flask equipped with a stirrer and a thermometer, and perform ultrasonic treatment for 30 min at an ultrasonic power of 200 W, and then stir the reaction at a temperature of 40 ° C and a stirring rate of 300 r / min for 2 h. After the reaction, cool the reaction product to room temperature, let it stand for 2 h, and then centrifuge it. Wash the precipitate twice with distilled water, and then place it in a vacuum drying oven and dry it at a temperature of 70 ° C for 4 h to obtain expanded pore hard carbon microspheres;

[0032] Step 4: Add 10 mmol nickel nitrate hexahydrate, 10 mmol cobalt acetate tetrahydrate and 150 mL deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 25 minutes at a temperature of 20°C and a stirring rate of 300 r / min, then add 8 g of pore-expanded hard carbon microspheres, 0.1 g of polyvinyl pyrrolidone and 0.2 mL of ethylenediamine and continue to stir and react for 5 minutes, then heat to 150°C and continue to stir and react for 5 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water twice, then place it in a vacuum drying oven, dry it at a temperature of 80°C for 6 hours, then place it in a tubular furnace, heat it to 450°C at a heating rate of 1°C / min and calcine it for 3 hours, then cool it with the furnace to obtain loaded hard carbon microspheres;

[0033] Step 5: Add 0.25g sodium alginate and 45mL deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 1h at a temperature of -5°C and a stirring rate of 300r / min, then add 20mL of a calcium chloride solution with a molar concentration of 0.2mol / L and continue to stir and react for 20min, then add 10g of loaded hard carbon microspheres, 0.42g of aniline and 0.02g of sodium dodecyl sulfate and continue to stir and react for 40min, then add 10mL of 1.5% ammonium persulfate solution dropwise while stirring, control the dropping rate to 1 drop / s, continue to stir and react for 6h after the addition is completed, and then freeze-dry to obtain a hard carbon negative electrode material for a fast-charging sodium ion battery.

[0034] Embodiment 2:

[0035] This embodiment is a method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery, comprising the following steps:

[0036] Step 1: 11g of melamine and 52mL of a 39% formaldehyde solution are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 22°C and a stirring rate of 350r / min for 22min, and then the mixture is heated to 62°C and stirred for 2.5h. Then, 4g of polyvinyl alcohol, 110mL of deionized water and 7mL of anhydrous acetic acid are added and stirred for 1.2h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed twice with distilled water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven and dried at 52°C for 2.5h to obtain a melamine formaldehyde resin.

[0037] Step 2: 10 g of melamine formaldehyde resin and 1.1 g of urea were mixed evenly and placed in a tubular furnace, nitrogen was introduced for protection, and the temperature was raised to 750°C at a heating rate of 1.5°C / min and calcined for 5.5 h, and then cooled with the furnace to obtain high nitrogen hard carbon microspheres;

[0038] Step 3: Add 5 g of high nitrogen hard carbon microspheres and 90 mL of 10% hydrochloric acid solution to a three-necked flask equipped with a stirrer and a thermometer, and perform ultrasonic treatment for 35 min at an ultrasonic power of 225 W, and then stir the reaction at a temperature of 42 ° C and a stirring rate of 350 r / min for 2.5 h. After the reaction is completed, the reaction product is cooled to room temperature, and then allowed to stand for 2.5 h, and then centrifuged. The precipitate is washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 72 ° C for 4.5 h to obtain expanded pore hard carbon microspheres;

[0039] Step 4: Add 10 mmol nickel nitrate hexahydrate, 10 mmol cobalt acetate tetrahydrate and 165 mL deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 28 minutes at a temperature of 22°C and a stirring rate of 350 r / min, then add 9 g of pore-expanded hard carbon microspheres, 0.12 g of polyvinyl pyrrolidone and 0.4 mL of ethylenediamine and continue to stir and react for 9 minutes, then heat to 155°C and continue to stir and react for 5.5 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water twice, then place it in a vacuum drying oven, dry it at a temperature of 82°C for 7 hours, then place it in a tubular furnace, heat it to 500°C at a heating rate of 1.5°C / min and calcine it for 3.5 hours, then cool it with the furnace to obtain loaded hard carbon microspheres;

[0040] Step 5: Add 0.5g sodium alginate and 48mL deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 1.5h at a temperature of -3°C and a stirring rate of 350r / min, then add 25mL of a calcium chloride solution with a molar concentration of 0.4mol / L and continue to stir and react for 25min, then add 10g of loaded hard carbon microspheres, 0.65g of aniline and 0.03g of sodium dodecyl sulfate and continue to stir and react for 45min, then add 12mL of 2% ammonium persulfate solution dropwise while stirring, control the dropping rate to 1 drop / s, continue to stir and react for 7h after the addition is completed, and then freeze-dry to obtain a hard carbon negative electrode material for a fast-charging sodium ion battery.

[0041] Embodiment 3:

[0042] This embodiment is a method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery, comprising the following steps:

[0043] Step 1: 12g of melamine and 55mL of a 40% formaldehyde solution are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 25°C and a stirring rate of 400r / min for 25min, and then the mixture is heated to 65°C and stirred for 3h. Then, 5g of polyvinyl alcohol, 120mL of deionized water and 8mL of anhydrous acetic acid are added and stirred for 1.5h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed three times with distilled water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven and dried at 55°C for 3h to obtain a melamine formaldehyde resin.

[0044] Step 2: 10 g of melamine formaldehyde resin and 1.9 g of urea were mixed evenly and placed in a tubular furnace, nitrogen was introduced for protection, and the temperature was raised to 800 ° C at a heating rate of 2 ° C / min and calcined for 6 hours, and then cooled with the furnace to obtain high nitrogen hard carbon microspheres;

[0045] Step 3: Add 5 g of high nitrogen hard carbon microspheres and 100 mL of 15% hydrochloric acid solution to a three-necked flask equipped with a stirrer and a thermometer, and perform ultrasonic treatment for 40 min at an ultrasonic power of 250 W, and then stir the reaction for 3 h at a temperature of 45 ° C and a stirring rate of 400 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then allowed to stand for 3 h, and then centrifuged. The precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 75 ° C for 5 h to obtain pore-expanded hard carbon microspheres;

[0046] Step 4: Add 10 mmol nickel nitrate hexahydrate, 10 mmol cobalt acetate tetrahydrate and 180 mL deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 30 minutes at a temperature of 25°C and a stirring rate of 400 r / min, then add 10 g of expanded pore hard carbon microspheres, 0.15 g of polyvinyl pyrrolidone and 0.6 mL of ethylenediamine and continue to stir and react for 10 minutes, then heat to 160°C and continue to stir and react for 6 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 3 times, then place it in a vacuum drying oven, dry it at a temperature of 85°C for 8 hours, then place it in a tubular furnace, heat it to 550°C at a heating rate of 2°C / min and calcine it for 4 hours, then cool it with the furnace to obtain loaded hard carbon microspheres;

[0047] Step 5: Add 0.75g of sodium alginate and 50mL of deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 2h at a temperature of 0°C and a stirring rate of 400r / min, then add 30mL of a calcium chloride solution with a molar concentration of 0.6mol / L and continue to stir and react for 30min, then add 10g of loaded hard carbon microspheres, 0.88g of aniline and 0.04g of sodium dodecyl sulfate and continue to stir and react for 50min, then add 15mL of 2.5% ammonium persulfate solution dropwise while stirring, control the drop acceleration rate to 2 drops / s, continue to stir and react for 8h after the addition is completed, and then freeze-dry to obtain a hard carbon negative electrode material for a fast-charging sodium ion battery.

[0048] Comparative Example 1:

[0049] This comparative example is a method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery, comprising the following steps:

[0050] Step 1: 12g of melamine and 55mL of a 40% formaldehyde solution are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 25°C and a stirring rate of 400r / min for 25min, and then the mixture is heated to 65°C and stirred for 3h. Then, 5g of polyvinyl alcohol, 120mL of deionized water and 8mL of anhydrous acetic acid are added and stirred for 1.5h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed three times with distilled water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven and dried at 55°C for 3h to obtain a melamine formaldehyde resin.

[0051] Step 2: Mix 10g of melamine formaldehyde resin evenly and place it in a tubular furnace, introduce nitrogen protection, and heat to 800℃ at a heating rate of 2℃ / min and calcine for 6h, then cool with the furnace to obtain a hard carbon negative electrode material for fast-charging sodium-ion batteries.

[0052] Comparative Example 2:

[0053] This comparative example is a method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery, comprising the following steps:

[0054] Step 1: 12g of melamine and 55mL of a 40% formaldehyde solution are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 25°C and a stirring rate of 400r / min for 25min, and then the mixture is heated to 65°C and stirred for 3h. Then, 5g of polyvinyl alcohol, 120mL of deionized water and 8mL of anhydrous acetic acid are added and stirred for 1.5h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed three times with distilled water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven and dried at 55°C for 3h to obtain a melamine formaldehyde resin.

[0055] Step 2: Mix 10g of melamine formaldehyde resin and 1.9g of urea evenly and place them in a tubular furnace. Pass nitrogen protection and heat to 800℃ at a heating rate of 2℃ / min and calcine for 6h. Then cool with the furnace to obtain a hard carbon negative electrode material for fast-charging sodium-ion batteries.

[0056] Comparative Example 3:

[0057] This comparative example is a method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery, comprising the following steps:

[0058] Step 1: 12g of melamine and 55mL of a 40% formaldehyde solution are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 25°C and a stirring rate of 400r / min for 25min, and then the mixture is heated to 65°C and stirred for 3h. Then, 5g of polyvinyl alcohol, 120mL of deionized water and 8mL of anhydrous acetic acid are added and stirred for 1.5h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed three times with distilled water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven and dried at 55°C for 3h to obtain a melamine formaldehyde resin.

[0059] Step 2: 10 g of melamine formaldehyde resin and 1.9 g of urea were mixed evenly and placed in a tubular furnace, nitrogen was introduced for protection, and the temperature was raised to 800 ° C at a heating rate of 2 ° C / min and calcined for 6 hours, and then cooled with the furnace to obtain high nitrogen hard carbon microspheres;

[0060] Step 3: Add 5 g of high nitrogen hard carbon microspheres and 100 mL of 15% hydrochloric acid solution to a three-necked flask equipped with a stirrer and a thermometer, and perform ultrasonic treatment for 40 min at an ultrasonic power of 250 W, and then stir the reaction for 3 h at a temperature of 45 ° C and a stirring rate of 400 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then allowed to stand for 3 h, and then centrifuged. The precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 75 ° C for 5 h to obtain pore-expanded hard carbon microspheres;

[0061] Step 4: Add 10 mmol nickel nitrate hexahydrate and 180 mL deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 30 minutes at a temperature of 25°C and a stirring rate of 400 r / min, then add 10 g of pore-expanded hard carbon microspheres, 0.15 g of polyvinyl pyrrolidone and 0.6 mL of ethylenediamine and continue to stir and react for 10 minutes, then heat to 160°C and continue to stir and react for 6 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate 3 times with distilled water, then place it in a vacuum drying oven, dry it at a temperature of 85°C for 8 hours, then place it in a tubular furnace, heat it to 550°C at a heating rate of 2°C / min and calcine it for 4 hours, then cool it with the furnace to obtain loaded hard carbon microspheres, and obtain a hard carbon negative electrode material for fast-charging sodium ion batteries.

[0062] Comparative Example 4:

[0063] This comparative example is a method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery, comprising the following steps:

[0064] Step 1: 12g of melamine and 55mL of a 40% formaldehyde solution are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 25°C and a stirring rate of 400r / min for 25min, and then the mixture is heated to 65°C and stirred for 3h. Then, 5g of polyvinyl alcohol, 120mL of deionized water and 8mL of anhydrous acetic acid are added and stirred for 1.5h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed three times with distilled water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven and dried at 55°C for 3h to obtain a melamine formaldehyde resin.

[0065] Step 2: 10 g of melamine formaldehyde resin and 1.9 g of urea were mixed evenly and placed in a tubular furnace, nitrogen was introduced for protection, and the temperature was raised to 800 ° C at a heating rate of 2 ° C / min and calcined for 6 hours, and then cooled with the furnace to obtain high nitrogen hard carbon microspheres;

[0066] Step 3: Add 5 g of high nitrogen hard carbon microspheres and 100 mL of 15% hydrochloric acid solution to a three-necked flask equipped with a stirrer and a thermometer, and perform ultrasonic treatment for 40 min at an ultrasonic power of 250 W, and then stir the reaction for 3 h at a temperature of 45 ° C and a stirring rate of 400 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then allowed to stand for 3 h, and then centrifuged. The precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 75 ° C for 5 h to obtain pore-expanded hard carbon microspheres;

[0067] Step 4: Add 10 mmol nickel nitrate hexahydrate, 10 mmol cobalt acetate tetrahydrate and 180 mL deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 30 minutes at a temperature of 25°C and a stirring rate of 400 r / min, then add 10 g of expanded pore hard carbon microspheres, 0.15 g of polyvinyl pyrrolidone and 0.6 mL of ethylenediamine and continue to stir and react for 10 minutes, then heat to 160°C and continue to stir and react for 6 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 3 times, then place it in a vacuum drying oven, dry it at a temperature of 85°C for 8 hours, then place it in a tubular furnace, heat it to 550°C at a heating rate of 2°C / min and calcine it for 4 hours, then cool it with the furnace to obtain a fast-charging sodium-ion battery hard carbon negative electrode material.

[0068] Comparative Example 5:

[0069] This comparative example is a method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery, comprising the following steps:

[0070] Step 1: 12g of melamine and 55mL of a 40% formaldehyde solution are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at 25°C and a stirring rate of 400r / min for 25min, and then the mixture is heated to 65°C and stirred for 3h. Then, 5g of polyvinyl alcohol, 120mL of deionized water and 8mL of anhydrous acetic acid are added and stirred for 1.5h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed three times with distilled water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven and dried at 55°C for 3h to obtain a melamine formaldehyde resin.

[0071] Step 2: 10 g of melamine formaldehyde resin and 1.9 g of urea were mixed evenly and placed in a tubular furnace, nitrogen was introduced for protection, and the temperature was raised to 800 ° C at a heating rate of 2 ° C / min and calcined for 6 hours, and then cooled with the furnace to obtain high nitrogen hard carbon microspheres;

[0072] Step 3: Add 5 g of high nitrogen hard carbon microspheres and 100 mL of 15% hydrochloric acid solution to a three-necked flask equipped with a stirrer and a thermometer, and perform ultrasonic treatment for 40 min at an ultrasonic power of 250 W, and then stir the reaction for 3 h at a temperature of 45 ° C and a stirring rate of 400 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then allowed to stand for 3 h, and then centrifuged. The precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 75 ° C for 5 h to obtain pore-expanded hard carbon microspheres;

[0073] Step 4: Add 10 mmol nickel nitrate hexahydrate, 10 mmol cobalt acetate tetrahydrate and 180 mL deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 30 minutes at a temperature of 25°C and a stirring rate of 400 r / min, then add 10 g of expanded pore hard carbon microspheres, 0.15 g of polyvinyl pyrrolidone and 0.6 mL of ethylenediamine and continue to stir and react for 10 minutes, then heat to 160°C and continue to stir and react for 6 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 3 times, then place it in a vacuum drying oven, dry it at a temperature of 85°C for 8 hours, then place it in a tubular furnace, heat it to 550°C at a heating rate of 2°C / min and calcine it for 4 hours, then cool it with the furnace to obtain loaded hard carbon microspheres;

[0074] Step 5: Add 0.75g of sodium alginate and 50mL of deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a constant pressure dropping funnel, introduce nitrogen protection, and stir the reaction for 2h at a temperature of 0°C and a stirring rate of 400r / min. Then, add 10g of loaded hard carbon microspheres, 0.88g of aniline and 0.04g of sodium dodecyl sulfate and continue to stir the reaction for 50min. Then, add 15mL of 2.5% ammonium persulfate solution dropwise while stirring, and control the dropping rate to 2 drops / s. After the addition is completed, continue to stir the reaction for 8h, and then freeze-dry to obtain a hard carbon negative electrode material for a fast-charging sodium ion battery.

[0075] The hard carbon negative electrode material, conductive carbon black and PVDF binder of the fast-charged sodium ion battery of Examples 1-3 and Comparative Examples 1-5 were mixed in a mass ratio of 7:2:1 and added to N-methylpyrrolidone and stirred to form a slurry. The obtained slurry was then scraped on the surface of the copper foil, and then dried, cut, pressed and vacuum dried to obtain a negative electrode sheet. A metal sodium sheet was used as a positive electrode sheet, 1M NaPF6-EC / DMC (v / v, 1:1) was used as an electrolyte, and Celgard 2400 was used as a diaphragm. A CR2016 button battery was assembled in a glove box, and the battery was left to stand for 24 hours and then subjected to an electrochemical performance test at 0.1A / g. The test results are shown in the following table:

[0076]

[0077] Referring to the data in the above table, it can be seen that the hard carbon negative electrode material of the fast-charged sodium ion battery of the present invention has excellent capacity and excellent cycle stability;

[0078] According to the comparison between Comparative Example 1 and Comparative Example 2, it can be seen that the addition of urea can further dope the N element, thereby increasing the capacity of the hard carbon negative electrode material of the fast-charged sodium-ion battery;

[0079] According to the comparison between Comparative Example 2 and Comparative Example 3, it can be seen that after the high nitrogen hard carbon microspheres are expanded with hydrochloric acid solution, doping with nickel-based metal oxides can further improve the capacity of the hard carbon negative electrode material of the fast-charged sodium ion battery; however, the doped nickel-based metal oxide is prone to volume expansion, resulting in poor cycle stability;

[0080] According to the comparison between Comparative Example 3 and Comparative Example 4, it can be seen that after the high nitrogen hard carbon microspheres are expanded with hydrochloric acid solution, doping with nickel and cobalt-based bimetallic oxides can further improve the capacity of the hard carbon negative electrode material of the fast-charged sodium ion battery; however, the doped nickel-based metal oxide is prone to volume expansion, resulting in poor cycle stability;

[0081] According to the comparison between Comparative Example 4 and Comparative Example 5, it can be seen that after the composite gel of sodium alginate and polyaniline cross-linked network is wrapped using sodium alginate and aniline, the volume expansion of the metal oxide is inhibited, and the cycle stability of the hard carbon negative electrode material of the fast-charged sodium ion battery can be greatly improved;

[0082] According to the comparison between Example 3 and Comparative Example 5, it can be seen that the use of calcium chloride solution can improve the conductivity of the composite gel, thereby further improving the capacity of the hard carbon negative electrode material of the fast-charging sodium ion battery.

[0083] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0084] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery, characterized in that: The following steps are involved: Step 1: adding melamine and formaldehyde solution to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introducing nitrogen protection, stirring and reacting for 20-25 minutes at a temperature of 20-25° C. and a stirring rate of 300-400 r / min, then heating to 60-65° C. and continuing to stir and react for 2-3 hours, then adding polyvinyl alcohol, deionized water and anhydrous acetic acid and continuing to stir and react for 1-1.5 hours, cooling the reaction product to room temperature after the reaction is completed, then centrifuging, washing the precipitate with distilled water and anhydrous ethanol for 2-3 times in sequence, then placing it in a vacuum drying oven, and drying it at a temperature of 50-55° C. for 2-3 hours to obtain melamine formaldehyde resin; Step 2: After melamine formaldehyde resin and urea are mixed evenly, they are placed in a tubular furnace, nitrogen is introduced for protection, and the temperature is raised to 700-800°C at a heating rate of 1-2°C / min and calcined for 5-6 hours, and then cooled in the furnace to obtain high nitrogen hard carbon microspheres; Step 3: Add high nitrogen hard carbon microspheres and hydrochloric acid solution to a three-necked flask equipped with a stirrer and a thermometer, and perform ultrasonic treatment for 30-40 minutes at an ultrasonic power of 200-250W, and then stir the reaction at a temperature of 40-45°C and a stirring rate of 300-400r / min for 2-3 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then allowed to stand for 2-3 hours, and then centrifuged. The precipitate is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 70-75°C for 4-5 hours to obtain expanded pore hard carbon microspheres; Step 4: Add nickel nitrate hexahydrate, cobalt acetate tetrahydrate and deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 25-30 minutes at a temperature of 20-25°C and a stirring rate of 300-400r / min, then add pore-expanded hard carbon microspheres, polyvinyl pyrrolidone and ethylenediamine and continue to stir and react for 5-10 minutes, then heat to 150-160°C and continue to stir and react for 5-6 hours, after the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 2-3 times, then place it in a vacuum drying oven, dry it at a temperature of 80-85°C for 6-8 hours, then place it in a tubular furnace, heat it to 450-550°C at a heating rate of 1-2°C / min and calcine it for 3-4 hours, then cool it with the furnace to obtain loaded hard carbon microspheres; Step 5: Add sodium alginate and deionized water to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a constant pressure dropping funnel, introduce nitrogen protection, stir and react for 1-2 hours at a temperature of -5-0°C and a stirring rate of 300-400r / min, then add calcium chloride solution and continue stirring and reacting for 20-30 minutes, then add loaded hard carbon microspheres, aniline and sodium dodecyl sulfate and continue stirring and reacting for 40-50 minutes, then add ammonium persulfate solution dropwise while stirring, control the dropping rate to 1-2 drops / s, continue stirring and reacting for 6-8 hours after the addition is completed, and then freeze-dry to obtain a hard carbon negative electrode material for a fast-charging sodium ion battery.

2. The method for preparing a hard carbon negative electrode material for a fast-charged sodium ion battery according to claim 1, characterized in that: The usage ratio of the melamine, formaldehyde solution, polyvinyl alcohol, deionized water and anhydrous acetic acid in step 1 is 10-12 g: 50-55 mL: 2-5 g: 100-120 mL: 6-8 mL.

3. The method for preparing a hard carbon negative electrode material for a fast-charged sodium ion battery according to claim 1, characterized in that: The mass fraction of the formaldehyde solution in step 1 is 37-40%.

4. The method for preparing a hard carbon negative electrode material for a fast-charged sodium ion battery according to claim 1, characterized in that: The usage ratio of the melamine formaldehyde resin and urea in step 2 is 10g:0.3-1.9g.

5. The method for preparing a hard carbon negative electrode material for a fast-charging sodium ion battery according to claim 1, characterized in that: The dosage ratio of the high nitrogen hard carbon microspheres and the hydrochloric acid solution in step 3 is 5g:80-100mL.

6. The method for preparing a hard carbon negative electrode material for a fast-charged sodium ion battery according to claim 1, characterized in that: The mass fraction of the hydrochloric acid solution in step 3 is 5-15%.

7. The method for preparing a hard carbon negative electrode material for a fast-charged sodium ion battery according to claim 1, characterized in that: The usage ratio of the nickel nitrate hexahydrate, cobalt acetate tetrahydrate, deionized water, expanded pore hard carbon microspheres, polyvinyl pyrrolidone and ethylenediamine in step 4 is 10mmol:10mmol:150-180mL:8-10g:0.1-0.15g:0.2-0.6mL.

8. The method for preparing a hard carbon negative electrode material for a fast-charged sodium ion battery according to claim 1, characterized in that: The dosage ratio of the sodium alginate, deionized water, calcium chloride solution, supported hard carbon microspheres, aniline, sodium dodecyl sulfate and ammonium persulfate solution in step five is 0.25-0.75 g: 45-50 mL: 20-30 mL: 10 g: 0.42-0.88 g: 0.02-0.04 g: 10-15 mL.

9. The method for preparing a hard carbon negative electrode material for a fast-charged sodium ion battery according to claim 1, characterized in that: The molar concentration of the calcium chloride solution in step 5 is 0.2-0.6 mol / L; the mass fraction of the ammonium persulfate solution is 1.5-2.5%.

10. A hard carbon negative electrode material for a fast-charging sodium ion battery, characterized in that: The fast-charging sodium-ion battery hard carbon negative electrode material is prepared according to the method for preparing the fast-charging sodium-ion battery hard carbon negative electrode material according to any one of claims 1-9.

Citation Information

Patent Citations

  • Hard carbon-graphene composite negative electrode material for fast-charging sodium ion battery and preparation method of hard carbon-graphene composite negative electrode material

    CN117894946A

  • Electrode material for high-temperature-resistant secondary battery and preparation method of electrode material

    CN118248841A

  • Low-temperature fast-charging sodium-ion battery electrolyte and preparation method thereof

    CN118352638A

  • Preparation method of fruit-tree-based hard carbon negative electrode material of sodium-ion battery

    CN118598134A

  • Electrode for lithium secondary battery having encapsulated active materials and method of manufacturing the same

    KR102447011B1